2020
DOI: 10.1159/000506310
|View full text |Cite
|
Sign up to set email alerts
|

Employment in Myasthenia Gravis: A Systematic Literature Review and Meta-Analysis

Abstract: Introduction: Myasthenia gravis (MG) is an autoimmune disease whose period of typical onset is around 20–40 years (i.e., early onset), thus in the peak of working age, or around 60–80 years (i.e., late onset). However, the information on work-related issues and employment status are sparse and not systematically reported. Therefore, we performed a systematic literature review with meta-analysis to address the employment status of MG patients. Methods: We searched for papers reporting employment status on parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
(44 reference statements)
1
16
0
1
Order By: Relevance
“…Some of these over-the-counter medications, such as quinine and magnesium, have been shown in some instances to exacerbate MG [ 36 ]. In addition, the mean age at diagnosis was relatively high compared with the expected age of MG onset, [ 37 , 38 ]. Thus, it is possible that a subgroup analysis of a younger population with fewer comorbidities may have yielded different results.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these over-the-counter medications, such as quinine and magnesium, have been shown in some instances to exacerbate MG [ 36 ]. In addition, the mean age at diagnosis was relatively high compared with the expected age of MG onset, [ 37 , 38 ]. Thus, it is possible that a subgroup analysis of a younger population with fewer comorbidities may have yielded different results.…”
Section: Discussionmentioning
confidence: 99%
“…Literature [10] holds that intention refers to the intention and tendency that an individual has consciously planned to pursue or not pursue a specific goal to some extent. Literature [11] also puts forward that intention is the antecedent of behavior. Literature [12] verified that internship job satisfaction, internship job stress, and students' intention to choose jobs in hotel industry were significantly positively correlated and negatively correlated and discussed the regression model of students' intention to choose jobs in hotel industry.…”
Section: Related Workmentioning
confidence: 99%
“… 23 Moreover, in a meta-analysis of data from 3600 patients with MG, only 50% were in employment, which is low considering that the average age was ∼48 years. 17 In addition to the impact on the individual's socioeconomic status, the consequences of reduced productivity (presenteeism), absenteeism, or early retirement place a burden on society in terms of indirect costs, including disability benefits and costs incurred via the Family and Medical Leave Act in the USA. Published data on this topic are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, it has been shown that MG can have a negative impact on work performance and lead to unemployment, premature retirement, and reduced income. [17][18][19] However, there is a lack of data on the impact of MG treatments on work-related outcomes. Eculizumab, a terminal complement inhibitor indicated in the USA for adults with anti-AChR antibody-positive gMG, 20,21 has been shown to improve patients' abilities to conduct everyday activities.…”
Section: Introductionmentioning
confidence: 99%